Synthesis and Reactions of Five-Membered Heterocycles Using Phase Transfer Catalyst (PTC) Techniques - Ahmed M. El-Sayed; Omyma A. Abd Allah; Ahmed M. M. El-Saghier; Shaaban K. Mohamed (Journal of Chemistry)
Phase transfer catalysts (PTCs) have been widely used for the synthesis of organic compounds particularly in both liquid-liquid and solid-liquid heterogeneous reaction mixtures. They are known to accelerate reaction rates by facilitating formation of interphase transfer of species and making reactions between reagents in two immiscible phases possible. Application of PTC instead of traditional technologies for industrial processes of organic synthesis provides substantial benefits for the environment. On the basis of numerous reports it is evident that phase-transfer catalysis is the most efficient way for generation and reactions of many active intermediates. In this review we report various uses of PTC in syntheses and reactions of five-membered heterocycles compounds and their multifused rings.